Epidemiology and Determinants of Vitamin D Deficiency in Eastern Nepal: A Community-Based, Cross-Sectional Study - O. Sherchand; J. K. Baranwal; B. Gelal (International Journal of Endocrinology)
Objective. To estimate the prevalence of vitamin D deficiency in the eastern part of Nepal and identify the sociodemographic factors associated with it. Methods. A descriptive cross-sectional study was carried out among 324 participants between the ages 18 and 65 years from the Sunsari and Morang districts of Nepal. A semi-structured questionnaire helped obtain sociodemographic data followed by anthropometric measurements and blood sampling. 25(OH)D level was measured by chemiluminescence immunoassay (CLIA) via a fully automated Maglumi 1000 analyzer (SNIBE Co., Ltd., China). Serum 25(OH)D was classified as deficient, insufficient, and sufficient (<20 ng/ml, 20–29 ng/ml, and 30–100 ng/ml, respectively). The chi-square test was used to analyze the sociodemographic variables followed by a post hoc analysis. Significant variables were subjected to multivariate logistic regression. Result. 181(55.9%) of the study population had vitamin D deficiency. There was significant association between vitamin D status and time of maximum sun exposure (chi square test = 11.1, p=0.02), duration of sun exposure (chi-square test = 15.1, p=0.004), type of meat intake (Fisher’s exact test is 16.4, p=0.01), frequency of fish intake (Fisher’s exact test is 19.3, p=0.001), and frequency of dairy intake (chi-square test=11.2, p=0.02). In multivariate regression, consumption of dairy products ≥3/week had lower OR (95% CI) (0.3(0.1–0.8) p:0.02) and weekly fish consumption had lower OR (95% CI) (0.06(0.008–0.6) p:0.01) for vitamin D deficiency. Conclusion. The prevalence of vitamin D deficiency was relatively high in eastern Nepal. This highlights the need to create public awareness regarding the importance of bare skin sun exposure, nutritional sources of vitamin D, and the need to implement food fortification policies by the government.